2020
DOI: 10.1177/0142723720929810
|View full text |Cite
|
Sign up to set email alerts
|

The development of English as a heritage language: The role of chronological age and age of onset of bilingualism

Abstract: This study explores typically developing bilingual children’s performance in their English as a heritage language. The aim of this study is to advance our understanding of heritage language expectations and the role of chronological age and bilingual exposure. A broad range of receptive and expressive linguistic domains are investigated as a function of chronological age and age of onset of bilingualism. English–Hebrew typically developing bilingual children ( N = 240), ages 60–77 months, were compared to mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 77 publications
4
29
0
Order By: Relevance
“…Age of onset of the L2 (L2-AoO) was moderately correlated with early and with late structures but showed no effects in the two regression analyses. The absence of effects of L2-AoO on HL development confirms the findings of Armon-Lotem et al (2011) but contrasts with many studies reporting positive effects of later exposure to the L2 (Janssen et al 2015;Gagarina and Klassert 2018;Armon-Lotem et al 2020;Rodina et al 2020). More research is needed to explain these differences, e.g., by targeting the same structures and/or by using the same statistical model.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Age of onset of the L2 (L2-AoO) was moderately correlated with early and with late structures but showed no effects in the two regression analyses. The absence of effects of L2-AoO on HL development confirms the findings of Armon-Lotem et al (2011) but contrasts with many studies reporting positive effects of later exposure to the L2 (Janssen et al 2015;Gagarina and Klassert 2018;Armon-Lotem et al 2020;Rodina et al 2020). More research is needed to explain these differences, e.g., by targeting the same structures and/or by using the same statistical model.…”
Section: Discussionsupporting
confidence: 66%
“…One notable exception is the study by Armon-Lotem et al (2011) who found that the development of lexical and grammatical skills in heritage Russian children living in Germany and Israel was not influenced by AoO of the majority language. Subsequent studies (Janssen et al 2015;Gagarina and Klassert 2018;Armon-Lotem et al 2020;Rodina et al 2020) revealed consistent advantages of later L2-AoO for HL acquisition. Janssen et al (2015) found that heritage Russian children could better exploit case cues for understanding non-canonical OVS sentences in Russian if they had a later AoO of the L2 Hebrew or Dutch, which exhibit sparse inflectional case morphology and rigid SVO word order.…”
Section: Child-internal and Environmental Effects On Hl Acquisition Amentioning
confidence: 82%
See 1 more Smart Citation
“…The remaining forty-one children were randomly assigned to two groups, one experimental, whose members received BINARI, the other, a control group. Criteria for inclusion in the study were: (1) one of the parents had to be a native English speaker; (2) the child had to score at or above local bilingual standards (see below) on either the English or Hebrew standardized language screening test ( Armon-Lotem and Meir, 2016 ; Armon-Lotem et al, 2021 ); (3) the child had to score above 85 on the Raven Progressive Matrices non-verbal intelligence test ( Raven et al, 1998 ); (4) the child had to be exposed to the L2 for at least 24 months; and (5) the child did not have any history of a hearing impairment or parental concerns about language. Written informed consent was obtained from the parents, who also provided information about their child’s language development and background.…”
Section: Methodsmentioning
confidence: 99%
“…The CELF-Preschool-2 ( Wiig et al, 2004 ) consists of six subtests for concepts and following directions, word structure, expressive vocabulary, recalling sentences, sentence structure, and receptive and expressive word classes. Local bilingual standards for the Core Language Scores (CLS) of the CELF-Preschool-2 (with a cutoff point of -1.25 SD ) are available for English-Hebrew bilinguals ( Rose, 2018 ; Armon-Lotem et al, 2021 ). Data from 240 typically developing English-Hebrew bilingual children aged 5;0–6;5 years have been used to set the local standards for the CLS taking into account chronological age and age of onset of bilingualism, identifying the means and SDs which indicate typical development in English as a HL in Israel.…”
Section: Methodsmentioning
confidence: 99%